Pengembangan Sistem Informasi Monitoring Kehadiran Siswa (Studi pada : SMA Negeri 105 Jakarta) - Bayu Kurniawan; Satrio Agung Wicaksono; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Currently, SMAN 105 Jakarta still makes little use of the Information System in teaching and administrative activities. In solving these problems, the Student Attendance Information System was developed for SMAN 105 Jakarta. Currently SMAN 105 Jakarta only has a website that only displays school information and the limited features that can be provided on the website to support learning activities in schools directly and are limited to the interests of the ministry of education, not from the school directly. System development is carried out using the waterfall software development life cycle to develop Student Academic Information Systems. The system is built using the CodeIgniter framework and in the design of the application, UML is used to build requirements, use cases, and other supporting diagrams. Testing of functional requirements in this system is carried out using blackbox testing which produces valid results in testing these requirements. With the UAT assessment of stakeholders, it results in a score of up to 100% acceptance of the system being built which indicates that the system is acceptable to stakeholders.